From a nutraceutical and anti-nutritional perspective, can a grain soybean cultivar be used as vegetable soybean? - Ribera, Laura Matos [UNESP]; Filho, Arthur Bernardes Cecilio [UNESP]; Fernandes, Gustavo do Carmo [UNESP]; Aires, Eduardo Santana [UNESP]; Silva, Maiele Leandro da; Bonfim, Filipe Pereira Giardini [UNESP] (Univ Federal Santa Maria, 2024)
: Vegetable soybean has high nutritional value and offers functional benefits to human body. However, its use in cooking is still limited, mainly due to the lack of knowledge about its properties. In addition, the availability of cultivars for human consumption is reduced. Therefore, this study was conducted in Botucatu, Brazil, to assess the potential of grain soybean (GS) and dual-purpose soybean (DPS) cultivars for consumption as vegetable soybean (VS). Pods were harvested at R6 stage, and the contents of bioactive compounds (total phenolic compounds, flavonoids, antioxidant activity and proteins) and antinutritional components (nitrates, oxalate, alkaloids and tannins) were evaluated. The cultivars showed the same protein content, not differing statistically from each other, as well as for nitrate and oxalate. The content of phenolic compounds and total antioxidant activity of the SG cultivar differed statistically from the content of the DPS and VS cultivars, respectively. According to the results, the GS cultivar, with pods harvested at R6 stage, showed nutraceutical quality and contents of antinutritional similar to those of the two cultivars for the
Keywords: Glycine max L. Merrill; bioactive compounds; oxalate; nitrate; tannin.